Life in its fullness: Ecology, eschatology and ecodomy in a time of climate change - Rossing, Barbara R. (HTS teologiese studies, 2020)
Given the close relationship of ecodomy with other words that also derive from oikos – especially economy and ecology – the term ‘ecodomy’ opens a space for dialogue with other disciplines, especially economics and the physical and social sciences. The Greek Orthodox Ecumenical Patriarch Bartholomew I, the Archbishop of Constantinople, known as the ‘Green Patriarch’, identifies the climate change crisis as a ‘kairos moment’ for churches and the world, warning that the time is short for the world to take decisive action. We argue that the apocalyptic tradition of Scripture can help as we face this new kairos moment. The argument is that the biblical Book of Revelation sheds light in at least two ways: firstly, to frame this crisis in terms of eschatology, and secondly, to help us envision future hope for a new creation and life on earth. If ecodomy is eschatology put into practice, it can help us address the climate crisis. We can name our moment as a kairos moment, a moment of hope and urgency. And we can draw on the apocalyptic witness of Scripture to address this crisis, not with despair but with hope – hope for what the Gospel of John calls ‘abundant life’, hope for a renewal of the whole community of earth, the ecodomy, hope for ‘life in all its fullness’.Contribution: The focus of this article is on the ecodomical use of the term kairos. The coherence of this article is a triangulation of ecodomy, ecology and eschatology, where climate change is the epitome of the ecological crisis and kairos is the demand. This brings theology and nature into consonance.